Papillary carcinoma thyroid with fibromatosis/fasciitis-like stroma: Report of a rare case with review of literature - Nischitha Suvarna; Swathi Prabhu; Sarah Johnson; Vidya Monappa (Journal of Krishna Institute of Medical Sciences University)
Papillary Thyroid Carcinoma with Fibromatosis/Fasciitis-Like Stroma (PTC-FMS) represents a rare variant of Papillary Thyroid Carcinoma (PTC). Recently, these tumours are further divided into two variants: PTC with nodular fasciitis-like stroma and PTC with fibromatosis-like stroma. Within the framework of the WHO classification, these tumours are discussed under the umbrella term of PTC with fibromatosis/fasciitis-like/desmoid type stroma. As the epithelial component can be missed on FNAC/ needle biopsy, there exists a risk of misdiagnosing this tumour as mesenchymal lesions. This case report presents a novel case of PTC-FMS along with a concise review of relevant literature.